Feasibility analysis of early temporal kinetics as a surrogate marker for breast tumor type, grade, and aggressiveness. Issue 6 (27th November 2017) - Heacock, Laura; Lewin, Alana A.; Gao, Yiming; Babb, James S.; Heller, Samantha L.; Melsaether, Amy N.; Bagadiya, Neeti; Kim, Sungheon G.; Moy, Linda
Abstract : Background: Screening breast MRI has been shown to preferentially detect high‐grade ductal carcinoma in situ (DCIS) and invasive carcinoma, likely due to increased angiogenesis resulting in early initial uptake of contrast. As interest grows in abbreviated screening breast MRI (AB‐MRI), markers of early contrast washin that can predict tumor grade and potential aggressiveness are of clinical interest. Purpose: To evaluate the feasibility of using the initial enhancement ratio (IER) as a surrogate marker for tumor grade, hormone receptor status, and prognostic markers, as an initial step to being incorporated into AB‐MRI. Study Type: Retrospective. Subjects: In all, 162 women (mean 55.0 years, range 32.8–87.7 years) with 187 malignancies imaged January 2012–November 2015. Field Strength/Sequence: Images were acquired at 3.0T with a T1 ‐weighted gradient echo fat‐suppressed‐volume interpolated breath‐hold sequence. Assessment: Subjects underwent dynamic contrast‐enhanced breast MRI with a 7‐channel breast coil. IER (% signal increase over baseline at the first postcontrast acquisition) was assessed and correlated with background parenchymal enhancement, washout curves, stage, and final pathology. Statistical Tests: Chi‐square test, Spearman rank correlation, Mann–Whitney U ‐tests, Bland–Altman analysis, and receiver operating characteristic curve analysis. Results: IER was higher for invasive cancer than for DCIS (R1/R2, P < 0.001). IER increased with tumor grade (R1: r  = 0.56, P < 0.001, R2: r  = 0.50, P < 0.001), as ki‐67 increased (R1: r  = 0.35, P < 0.001; R2 r  = 0.35, P < 0.001), and for node‐positive disease (R1/R2, P  = 0.001). IER was higher for human epidermal growth factor receptor two‐positive and triple negative cancers than for estrogen receptor‐positive / progesterone receptor‐positive tumors (R1 P < 0.001–0.002; R2 P  = 0.0.001–0.011). IER had higher sensitivity (80.6% vs. 75.5%) and specificity (55.8% vs. 48.1%) than washout curves for positive nodes, higher specificity (48.1% vs. 36.5%) and positive predictive value (70.2% vs. 66.7%) for high ki‐67, and excellent interobserver agreement (intraclass correlation coefficient = 0.82). Data Conclusion: IER, a measurement of early contrast washin, is associated with higher‐grade malignancies and tumor aggressiveness and might be potentially incorporated into an AB‐MRI protocol. Level of Evidence: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1692–1700.